Sustainable development on production and characterization of metal matrix composites using stir casting - Rajan, Raj Thilak Krishnan; Ramesh, S; Boppana, Satish Babu; Krishnan, Pradeep Kumar (Journal of physics communications, 2023)
In this study, four different combinations of aluminium metal matrix composites (AMCs) were produced using a computerized stir casting process. The feasibility of using car Scrap Aluminium Engine Head (SAEH) as matrix material, Fresh Alumina Catalyst (FAC) and Spent Alumina Catalyst (SAC) from petrochemical industries as reinforcement material were investigated. The physical and mechanical properties of the cast samples were tested through density, hardness, tensile, compression, and impact test. Microstructural investigations were carried out using an optical microscope, scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD). Differential thermal analysis (DTA) and Thermo gravimetric analysis (TGA) were also conducted to justify the results obtained. The results indicated that SAEH reinforced with 5 wt% SAC exhibited lower porosity (2.6%) and higher Brinell hardness (71.5 BHN), Vickers hardness (307.1 VHN), tensile strength (217 MPa), and compressive strength (426 MPa) than other composites. Additionally, this composite showed the highest impact strength (0.02375 J mm −2 ) and DTA value (568.5 μ V mg −1 ). The TGA result showed that all composites had high thermal stability, with the SAC-reinforced composites having the highest thermal stability (100.13%).